A systematic review of microfinance interventions and violence against women: results from low- and middle-income contexts - Nancy Glass; Lori Heise; Michele R Decker; Anaise Williams; Grace Wamue-Ngare; Abigael Malelu-Gitau; Cynthia Edeh; Yurie Aiura; Tabitha Gitahi; Joan Rakuomi (BMJ Global Health)
Background Women’s economic empowerment is a longstanding strategy for reducing violence against women and girls (VAWG). Microfinance, the provision of credit and savings opportunities to low-resourced populations, is often delivered in combination with other types of programming, such as gender training, making it hard to assess impact alone and/or in combination with other programming. We assess the effectiveness of diverse forms of microfinance intervention delivery on VAWG.Methods The systematic review covered nine databases and grey literature sources for articles published between January 2015 and August 2023. Eligible studies were English language experimental and quasi-experimental evaluations of microfinance programming with a VAWG outcome conducted within a low- or middle-income country. Study members reviewed in Covidence and extracted summary data. A parallel qualitative scoping review was conducted.Results A total of 3288 studies were reviewed, of which 16 were eligible, with an additional nine grey literature sourced studies (n=25). Most assessed group microfinance (n=16) in relation to intimate partner violence (n=20). Across studies, there were 38 trial arm comparisons, of which 30 were from low-bias studies, inclusive of 15 that identified economic impact. Only 24% (n=9) of comparisons assessed impacts of microfinance programming delivered alone; six null and three protective. Impacts of adding supplemental non-economic programming to microfinance (n=14) and delivering microfinance with non-economic programming (n=15) had mixed results. Qualitative synthesis highlighted the benefits and harms of microfinance.Conclusion Microfinance can reduce VAWG in some cases; however, overall results are mixed with the majority being null results. Several complexities emerged: variability in both microfinance programme delivery, often involving supplementary programming, and measurement of economic impact on the pathway to reducing VAWG. Both reflect the expanded programming underway and must be considered for a nuanced understanding of microfinance’s VAWG impact. The review identifies a small but important evidence base of VAWG increasing due to programming. Varied supplemental non-economic programming was not consistently found to enhance the effectiveness of microfinance in reducing VAWG. Actionable gaps for future programmatic and evaluation work include examining differences across supplemental programming, populations, and outcomes.